The Legal and Economic Aspects of a Free Zone Setting Up Possibility in Ibrahim Al-Khalil Area in The Kurdistan Region of Iraq - Hawre Kamal Muhammed; Badr Mohammed Taher Mustafa (QALAAI ZANIST JOURNAL, 2021)
The topic of this research revolves around the possibility of proposing a law for free zones in the Kurdistan Region and the extent of the possibility of establishing them in the Ibrahim Khalil area from the economic and legal point of view, according to the Iraqi constitution of 2005, owing to the prominent role played by these regions in attracting foreign direct investment and achieving the economic development of the host country, and how developing countries like UAE and China benefited from the free zones to achieve these goals while Iraq failed. The research reached several results, most notably: there are administrative and financial obstacles to establish a free zone in the province, but generally there are available economic requirements for establishing a free zone in the Ibrahim Khalil area. Also, from a legal point of view, the establishment of free zones falls within the jurisdiction of the region’s authorities, and therefore the Kurdistan Parliament can legislate a law regarding the establishment of free zones in the region, according to the Iraqi constitution of 2005. The research also recommended series of proposals, most notably: Legislating a law on free zones by the Kurdistan Parliament of Iraq, and establishing a free zone in Ibrahim Khalil, and that the free zone be established by multinational companies according to the (B.O.T.) system. Key words: Free Zones Law, Foreign Direct Investment, Economic Development, Ibrahim Khalil Port, Kurdistan province of Iraq, Iraqi Constitution of 2005.